The role of pleiotropy and linkage in genes affecting a sexual ornament and bone allocation in the chicken. Issue 9 (9th April 2014) - Johnsson, M.; Rubin, C.‐J.; Höglund, A.; Sahlqvist, A.‐S.; Jonsson, K. B.; Kerje, S.; Ekwall, O.; Kämpe, O.; Andersson, L.; Jensen, P.; Wright, D.
Abstract Sexual selection and the ornaments that inform such choices have been extensively studied, particularly from a phenotypic perspective. Although more is being revealed about the genetic architecture of sexual ornaments, much still remains to be discovered. The comb of the chicken is one of the most widely recognized sexual ornaments, which has been shown to be correlated with both fecundity and bone allocation. In this study, we use a combination of multiple intercrosses between White Leghorn populations and wild‐derived Red Junglefowl to, first, map quantitative trait loci (QTL) for bone allocation and, second, to identify expression QTL that correlate and colocalize with comb mass. These candidate quantitative genes were then assessed for potential pleiotropic effects on bone tissue and fecundity traits. We identify genes that correlate with both relative comb mass and bone traits suggesting a combination of both pleiotropy and linkage mediates gene regulatory variation in these traits.